Acute abdomen after vertebroplasty-A rare complication - Zhao, Xiao-ming; Lou, Xiao-xiao; Chen, An-fa; Zhang, Yin-gang (Frontiers in Surgery, 2023)
Introduction：In recent years, as the concept of minimally invasive treatment has been accepted by the majority of patients, the application of percutaneous vertebroplasty in osteoporotic vertebral compression fractures has gradually increased, and the research on the adverse complications of bone cement leakage has gradually deepened. Case：Here we report a rare case of acute pancreatitis after vertebroplasty. The patient had no previous history of pancreatitis and presented with obvious abdominal pain after vertebroplasty. Abdominal CT examination revealed that the leaking bone cement penetrated the anterior wall of the L1 vertebral body into the diaphragm, and the heat released by the polymerization reaction caused inflammation and damage to the adjacent pancreas, resulting in poor blood flow to the pancreatic tissue and leading to acute pancreatitis. Early postoperative symptomatic treatment was given to the patient, and the corresponding symptoms were gradually relieved. During postoperative follow-up, the leaking cement did not degrade, but the patient had no symptoms. Conclusion：lesions of adjacent organs caused by bone cement leakage are rare, clinicians often ignore the association between such complications and vertebroplasty. This case report will play a certain guidance and reference role for clinicians.